Applied AVSWAT 2000 for assessment of pollutant load in Brantas River Basin, Indonesia - Sholichin, Mohammad; Othman, Faridah; Shirazi, S.M.; Akib, Shatirah; Harisuseno, Donny; Sisinggih, Dian (2011)
This paper presented the results of assessment pollutant load such as nutrient and phosphorus on Brantas River basin Indonesia. A Soil and Water Assessment Tool (SWAT) was choose to applied in this study due to successful for simulate the effect land used management from large watershed in many countries. Stream flow and sediment yield were calibrated for the 1991-2003 period and validated for the 2004-2006 period. The resulting statistical goodness-of-fit was evaluated with the Nash-Sutcliffe coefficient NS = 0.38 and R2 of the one-to-one line for monthly stream flow was 0.725. Results showed that annual average nutrient loads such as organic N, organic P, nitrate, sediment P increased in trend from 1991 to 2006. Simulated results showed that average annual nutrient load was 60.88 kg N/ha/yr for organic N, 11.64 kg N/ha/yr for Nitrate, 0.08 kg P/ha/yr for organic P and 0.25 kg P/ha/yr for soluble P, respectively. The most dominant type of land use contributing to increased nutrient load in rivers was the rice field. The water quality of Brantas River did not meet class II in term of nutrient parameters based on local water quality standard.